Malawi : 2006 Article IV Consultation and Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Nonobservance of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that Malawi is at a critical juncture following its progress on macroeconomic stability, attainment of the Heavily Indebted Poor Countries (HIPC) completion point in August 2006, and the recent launch of the Malawi Growth and Development Strategy, which outlines an ambitious agenda of structural reform to enhance growth and reduce poverty. This paper focuses on the three key challenges facing Malawi over the medium term, which frame macroeconomic policy over the near term.